The introduction of garden centres to the Hutt Valley - Jordan, Kate (Architectural History Aotearoa, 2022)
New Zealand gardening histories are frustratingly brief when discussing the shift in garden retailing in the post-war period. Often, only a mere sentence or paragraph considers the introduction of garden centres. Architectural historian Paul Walker provides an excellent example, writing "Drive-in suburban garden centres spread everywhere and displaced older modes of garden retailing – the central-city garden shops, local nurseries, and probably a good many of the bread-and-butter mail-order businesses have gone." He then moves on to another topic. This paper looks at this shift in garden retailing through three of the earliest garden centres in the Hutt Valley: Zenith, Twiglands and Kents. Each business represents different developments in garden retailing: a nursery that converted into a garden centre, a purpose-built garden centre, and a garden centre with a café. These developments changed how people shopped for plants and garden supplies and evoked various responses from their neighbourhoods. Interestingly the question asked time and again was - do garden centres contribute to the public good? In addition to regular historic sources such as newspapers and advertisements, this talk uses unusual sources such as files from local councils, the Town and Country Planning Appeal Board, and the Shops and Office Tribunal.